Efficient structural optimisation of a 20 MW wind turbine blade. Issue 4 (September 2020) - Scott, S; Greaves, P; Weaver, P M; Pirrera, A; Macquart, T
Abstract: This paper presents, through the structural design of a 20 MW wind turbine blade, a selection of novel analysis and optimisation methods for wind turbines. These methods are integrated in the software—A eroelastic T urbine O ptimisation M ethods (ATOM). A key feature is the novel, computationally-efficient piecewise linear model for running rapid design load case simulations (up to 16 times speed-up over conventional methods). Further, a comprehensive set of realistic design constraints is also proposed to ensure structural feasibility and aeroelastic stability. To demonstrate these methods, a sequential gradient-based optimisation process is employed, relying on the globally convergent method of moving asymptotes (GCMMA). The process begins with an aerodynamic optimisation to generate twist distributions, followed by an iterative loop during which load envelope updates and 'frozen-load' blade structural optimisations are performed independently. Aeroelastic loads are therefore considered, but are not directly optimised for. The present study investigates the structural design of a 20 MW wind turbine blade with hybrid carbon-glass spar caps. The optimised 122 m blade is found to have a mass of 83, 622 kg, which decreases to 81, 396 kg (-2.66%) with the addition of sweep. The GCMMA is found to converge successfully at each structural optimisation step. By contrast, the iterative loop is observed to oscillate, albeit within small bounds. Finally, results suggest that convergence of multi-step optimisation methods for aeroelastic blade design may not be guaranteed if design variables inducing aeroelastic couplings are considered.